Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1902/jop.2017.160751
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers and Bacteria Around Implants and Natural Teeth in the Same Individuals

Abstract: There were many similarities but, crucially, some differences in biomarker levels (IL-1β and sRANKL) and bacterial species between peri-implant and periodontal sites in the same individuals, suggesting similar pathogenic mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 47 publications
(66 reference statements)
5
46
1
Order By: Relevance
“…These are possible explanations for the similarity in PI, PD, and CBL among individuals in Groups 1 and 2. Among participants in Group 3, the most likely reason for the occurrence of peri-implantitis appeared to be poor oral hygiene maintenance, as dental plaque harbors pathogenic microbes (such as Porphyromonas gingivalis and Treponema denticola) that are associated with oral soft tissues inflammation and alveolar bone loss around teeth and implants (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…These are possible explanations for the similarity in PI, PD, and CBL among individuals in Groups 1 and 2. Among participants in Group 3, the most likely reason for the occurrence of peri-implantitis appeared to be poor oral hygiene maintenance, as dental plaque harbors pathogenic microbes (such as Porphyromonas gingivalis and Treponema denticola) that are associated with oral soft tissues inflammation and alveolar bone loss around teeth and implants (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study nearly 72% individuals in group‐2 reported to brush their teeth once daily and none of the individuals in either group reported to have ever used a dental floss. Studies have reported that a poor plaque control is associated with an increased frequency of pathogenic microbes (such as Prevotella intermedia , Treponema denticola , and Aggregatibacter actinomycetemcomitans ) that have been associated with the etiology of periodontitis as well as peri‐implantitis. It is also notable that although the number of individuals in group‐1 (approximately 78%) that reported to brush their teeth once daily was similar to those in group‐2 (approximately 72%), peri‐implant PPD and CBL were significantly higher among individuals in group‐1 than group‐2.…”
Section: Discussionmentioning
confidence: 99%
“…Published studies mostly suggest that biomarker and microbiological data are similar around natural teeth and intraosseous dental implants as long as the clinical health state is similar . A recent study by Gürlek and colleagues also stated that differences in bacterial species in the same individuals were evident. The present study revealed similar findings in the PICF and GCF samples.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation affecting the peri‐implant tissues causes mucositis and peri‐implantitis via similar inflammatory mechanisms acting in the pathogenesis of gingivitis and periodontitis. There are studies reporting similar content of the pathogenic bacteria in the biofilm around dental implants and natural teeth while differences in bacterial species in the same individuals were demonstrated recently suggesting distinct pathogenic mechanisms . It is also shown that presence of Aggregatibacter actinomycetemcomitans , Prevotella intermedia , Porphyromonas gingivalis , Treponema denticola , and Fusobacterium nucleatum at the implant sulcus was affected by the presence or absence of these microorganisms in the gingival crevice of adjacent teeth rather than other sites in the dentition …”
Section: Introductionmentioning
confidence: 99%